2003
DOI: 10.1074/jbc.m210581200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Reduction in β-Cell Mass Results in Two Distinct Outcomes over Time

Abstract: We have proposed that hyperglycemia-induced dedifferentiation of ␤-cells is a critical factor for the loss of insulin secretory function in diabetes. Here we examined the effects of the duration of hyperglycemia on gene expression in islets of partially pancreatectomized (Px) rats. Islets were isolated, and mRNA was extracted from rats 4 and 14 weeks after Px or sham Px surgery. Px rats developed different degrees of hyperglycemia; low hyperglycemia was assigned to Px rats with fed blood glucose levels less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(64 citation statements)
references
References 49 publications
11
53
0
Order By: Relevance
“…Thus, consistent with Taylor's results, our data revealed that DEX and exercise expanded b-cell mass via two independent mechanisms, contributing to the modulation of b-cell function in order to compensate for insulin resistance. Consistent with our results, Px rats exhibited abnormalities in b-cell function and mass, even though b-cell area and small b-cell clusters were increased (Laybutt et al 2003). The mechanism that impairs b-cell function and mass due to insulin resistance has not yet been clarified.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, consistent with Taylor's results, our data revealed that DEX and exercise expanded b-cell mass via two independent mechanisms, contributing to the modulation of b-cell function in order to compensate for insulin resistance. Consistent with our results, Px rats exhibited abnormalities in b-cell function and mass, even though b-cell area and small b-cell clusters were increased (Laybutt et al 2003). The mechanism that impairs b-cell function and mass due to insulin resistance has not yet been clarified.…”
Section: Discussionsupporting
confidence: 79%
“…Another possible mechanism to reduce b-cell mass is decreased expression of transcription factors, which are important for islet development, such as PDX-1, Neuro D and hepatic nuclear factor-1a (HNF-1a) (Laybutt et al 2003). Several studies have demonstrated that mRNA levels of these transcription factors were reduced by 50-60% in Px rats with 120 mg/dl glucose levels after 4 weeks from pancreatectomy (Jonsson et al 1994, Stoffers et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…According to this hypothesis, long-term adaptation of the ␤ cells to conditions of increased demand may be triggered by limited hyperglycemic excursions (35). These excursions elicit ␤ cell production of IL-1␤ (6) followed by Fas upregulation (3,7). At low concentrations of IL-1␤ and in the presence of FLIP, Fas engagement leads to ␤ cell proliferation (36) and enhanced function via NF-B and PDX-1, as shown in the present study.…”
Section: Discussionmentioning
confidence: 62%
“…Fas (CD95) is a cell surface receptor that plays a central role in the regulation of death in many cell types, including ␤ cells, and may be implicated in the development of type 1 and type 2 diabetes (3)(4)(5). Glucose-induced ␤ cell apoptosis in human islets involves IL-1␤-mediated up-regulation of Fas and subsequent interaction with the constitutively expressed Fas ligand (FasL) on neighboring ␤ cells (3,(6)(7)(8). Fas/FasL interaction leads to cleavage of procaspase-8, the most upstream caspase in the Fas apoptotic pathway.…”
mentioning
confidence: 99%
“…Furthermore, it is becoming increasingly apparent that many factors classically deemed type 1 diabetesspecific are also integral to the process of ␤ cell failure in type 2 diabetes patients. These include the effect of IL-1␤, Fas, and nuclear factor-B, endoplasmic reticulum stress, and increased expression of c-Myc (19)(20)(21)(22). Interestingly, polymorphisms in the Fas pathway have been associated recently with type 2 diabetes (23).…”
mentioning
confidence: 99%